The impact of teacher empowerment on schools’ innovation climate - Mokhlis, Safiek; Abdullah, Abdul Hakim (Journal of Education and Learning (EduLearn), 2025)
Teacher empowerment has been recognized as an imperative management practice to develop and implement innovations in schools. However, studies investigating the relationship between teacher empowerment and the innovation climate are scant, inhibiting the development of effective strategies to foster educational innovation. This study examines the impact of teacher empowerment on schools’ innovation climate in Malaysia. The sample consisted of 376 teachers who were randomly selected from 12 primary and secondary schools in Kuala Terengganu. Structural equation modeling analysis revealed a strong positive effect of teacher empowerment on innovation climate, wherein teacher empowerment predicted 50% of the variability in the innovation climate. Findings of this study suggest that school leaders should invest in empowering teachers through programs that value their perspectives and actively encourage contributions to foster an innovation climate.